Banana Stem Charcoal as Adsorbents Reduce Water Hardness Levels - Ronny, Ronny; Irfai, Irfai; Mahyudin, Dedi; Jasman, Jasman (Three E Science Institute, 2019)
One of the chemical parameters in the requirements of clean water is water hardness. Hardness is a term used in water containing cations that cause hardness. Generally, hardness caused by the presence of metals or cations which have a valence of 2, such as Fe, Sr, Mn, Ca and Mg. The purpose of this research is to determine the effect of banana stem charcoal as an adsorbent in reducing water hardness. The process of charcoal banana stem adsorbent dried under the sun for one week, and in the oven at 110°C for 24 hours to reduce moisture and moisture content. Next, to remove volatile materials, the hydrolyzed sample was heated at 400°C to become charcoal with 30 minutes in the furnace after which it was sieved with 106 µm and 250 µm sieves and stored in a desiccator. From the results of the study, it found that the banana charcoal adsorption process can reduce the water hardness level to reach 43.56% for the contact time of about 240 minutes with the thickness of the charcoal used around 5 cm. Then from the t-test analysis showed a significant difference before and after using banana stem charcoal as an adsorbent medium. Banana stem charcoal can be an alternative to adsorbent media to reduce the level of water pollution in addition to other media that commonly used.